Motif dan Kepuasan Generasi Z Kota Denpasar Dalam Mengikuti Akun Instagram @kisminb0ys - galileo, adam; Suryawati, I Gusti Agung Alit; Pradipta, Ade Devia (E-Jurnal Medium; Vol 3 No 1 (2022): Jurnal Ilmu Komunikasi Vol 3 No 1 Tahun 2022, 2022)
Instagram is a free photo and video sharing app that available on iPhone and Android. The different needs of each individual result in a variety of accounts on Instagram that share photos and videos to fulfill these needs. This study uses a descriptive quantitative method that aims to find out what motives of Generation Z in Denpasar City to follow @kisminb0ys Instagram account and gratifications of Generation Z in Denpasar City in following the @kisminb0ys Instagram account. The results show that there are five motives that can be satisfied, namely the social interaction motive, information seeking motive, communicatory utility motive, convenience utility motive, and the pass time motive. The motives that cannot be satisfied are the entertainment motives and the relaxation motives. Based on the results of this study, it can be said that Generation Z Denpasar City has got satisfaction in following the @kisminb0ys Instagram account. Keyword: Motives, Gratifications, Generation Z, @kisminb0ys